Picture the dead - Griffin, Adele (Sourcebooks Fire, 2010)
A young woman communicates with her brother who died in 1864 in order to find out what happened to her fiance, Will, whom the army said died in battle; and with the help of a spiritualist photographer and the spirit of Will, she attempts to piece together the mystery of what happened.